1997
DOI: 10.2337/diacare.20.3.438
|View full text |Cite
|
Sign up to set email alerts
|

Is Type II Diabetes Associated With an Increased Risk of Cognitive Dysfunction?: A critical review of published studies

Abstract: Type II (non-insulin-dependent) diabetes may be associated with impaired cognitive function. A detailed search of the literature has identified 19 controlled studies in which cognitive function in type II diabetes has been examined. The studies vary widely with respect to the nature of the diabetic populations studied and the psychological tests used. Thirteen studies demonstrated that the diabetic individuals performed more poorly in at least one aspect of cognitive function. The most commonly affected cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
296
3
8

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 485 publications
(323 citation statements)
references
References 0 publications
16
296
3
8
Order By: Relevance
“…Also consistent with previous findings [2,4,32], and as hypothesised, mean performance scores were lower for the diabetic than for the non-diabetic group for MMSE, the similarities subtest and each of the cognitive composite scores, with the exception of the verbal memory composite.…”
Section: Discussionsupporting
confidence: 91%
“…Also consistent with previous findings [2,4,32], and as hypothesised, mean performance scores were lower for the diabetic than for the non-diabetic group for MMSE, the similarities subtest and each of the cognitive composite scores, with the exception of the verbal memory composite.…”
Section: Discussionsupporting
confidence: 91%
“…There is accumulating evidence that diabetes, in addition to increasing the risk of cardiovascular disease, stroke and kidney failure, may also adversely affect brain function independently from atherosclerotic disease. To date, numerous studies have demonstrated that type 2 diabetes is associated with cognitive deficits (for example [2][3][4][5]). …”
Section: Introductionmentioning
confidence: 99%
“…Studies from various populations have consistently shown diabetes to be associated with cognitive deficits and dementia [1][2][3]. The pathophysiological mechanisms underlying this association are not fully understood, mainly because of the wide range of possible aetiologies.…”
Section: Introductionmentioning
confidence: 99%